Inventories, Production Smoothing, and the Flexible Accelerator - Darling, Paul; Lovell, Michael C. (Quarterly Journal of Economics, 1971)
Journal Article Inventories, Production Smoothing, and the Flexible Accelerator Get access Paul Darling, Paul Darling Bowdoin College Search for other works by this author on: Oxford Academic Google Scholar Michael C. Lovell Michael C. Lovell Wesleyan University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 85, Issue 2, May 1971, Pages 357–362, https://doi.org/10.2307/1880712 Published: 01 May 1971